Pengaruh Website Quality Terhadap Online Booking Intention dengan Mediasi E-Trust Pada Situs Booking.com di Kota Bukittinggi - Putri Nabila; Yasri Yasri (Jurnal Kajian Manajemen dan Wirausaha, 2019)
The purpose of this researches are to analyze: (1) Effect of website quality on online booking intention with Booking.com users. (2) Effect of e-trust on online booking intention with Booking.com users. (3) Effect of website quality on online booking intention by mediating e-trust on Booking.com users. This type of research is causative. This research was conducted in the city of Bukittinggi. The population in this study is all the people of the city of Bukittinggi who know about the Booking.com site or have a Booking.com application but have never made an online purchase. The sample used was 200 people using purposive sampling technique. The type of data in this study is primary data. Secondary data was collected through documentation, questionnaires and analyzed using the SmartPLS version 3.0 program. The results of this study indicate that: (1) Website quality has a positive and significant effect on e-trust, (2) Website quality has a positive but not significant effect on online booking intention, (3) E-trust has a positive and significant effect on online booking intention. Keywords: Website Quality,E-trust, Online Booking Intention